FAKTOR –FAKTOR YANG MEMENGARUHI PENEMPATAN PEGAWAI NEGRI SIPIL PADA SEKRETARIAT DAERAH KABUPATEN SINTANG - Fernando Nugroho E.42008030 (FISIP Universitas Tanjungpura Pontianak, 2022)
This discussion papera to study the process of staffing and the factors that influencethe success of implementation. In this study the authors wanted to formulate the problemis how the process of implementati on of Regional Secretariat staffing at Sintang in order to improvethe quality and quantity of employee performance. So that the purpose of this study was to analyze the process description of implementation and staffing policies in order to improvethe quality of employee performance in the Regional SecretariatSintang. This study uses a qualitative approach to research desctrictif methods . The authors concluded there are two (2) factors that influencethe success of policy implementationinthe placement of civil servants Regional Secretariat Sintang the internal an dexternal factors. At the pentup authors propose, some conclusions and suggestions related to the phenomenon under study. The authors concluded that the placement of civil servants has be implemented very effective for improving employee performance. Further more, the author gives some advice to the Regional Secretariat Sintang to help support the development of infrastructures and suggestionsin terms of personnel transfers. Keyword : Placement, Movements, Civil Servants.